RELATIONSHIPS BETWEEN CONFLICT BEHAVIOR AND CONFLICT SITUATIONS IN THE STUDENT COMMUNITY (American Journal of Interdisciplinary Research and Development, 2022)
This article discusses the relationship between conflict behavior and conflict situations in the student community. Based on pedagogical data and written sources, the author clarified the problem on the basis of available scientific literature and studied the existing specific aspects of the relationship between conflict behavior and conflict situations in the student community.